Greece : Staff Report for the 1999 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This 1999 Article IV Consultation with Greece highlights that the 'regime switch' represented by the drachma devaluation, ERM entry, and the accompanying strengthening of policies was deemed essential also by the staff, both for competitiveness and confidence reasons. The monetary policy stance centered on high interest rates and a strong drachma-has been tight, contributing to the anti-inflationary effort. The growth of mortgage and consumer lending has been particularly brisk, raising Bank of Greece concerns about its potential inflationary impact. On structural reforms, progress has been visible with regard to privatization and some aspects of public enterprise restructuring, but much remains to be done, while broad social security and labor market reforms remain largely on hold. The IMF staff recognized that, having eschewed what it saw as the preferable option of an immediate post-devaluation tightening of the fiscal stance, the authorities had left themselves with limited policy tools to restrain inflation within the short time span available to the Maastricht test date.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet